Analogies, metaphors, and wondering about the future: Lay sense-making around synthetic meat. (July 2015) - Marcu, Afrodita; Gaspar, Rui; Rutsaert, Pieter; Seibt, Beate; Fletcher, David; Verbeke, Wim; Barnett, Julie
Drawing on social representations theory, we explore how the public make sense of the unfamiliar, taking as the example a novel technology: synthetic meat. Data from an online deliberation study and eighteen focus groups in Belgium, Portugal and the UK indicated that the various strategies of sense-making afforded different levels of critical thinking about synthetic meat. Anchoring to genetic modification, metaphors like 'Frankenfoods' and commonplaces like 'playing God' closed off debates around potential applications of synthetic meat, whereas asking factual and rhetorical questions about it, weighing up pragmatically its risks and benefits, and envisaging changing current mentalities or behaviours in order to adapt to scientific developments enabled a consideration of synthetic meat's possible implications for agriculture, environment, and society. We suggest that research on public understanding of technology should cultivate a climate of active thinking and should encourage questioning during the process of sense-making to try to reduce unhelpful anchoring.